Research on the Bonding Performance of UHPC–NC Interfaces With Different Sizes of Grooves - Yang, Jun; Xia, Junrun; Cheng, Chongsheng; Wang, Jieyun; Zhang, Jie; Wang, Gang (Frontiers in Materials, 2022)
The interfacial treatment at the interface between normal concrete (NC) and Ultra-high-performance concrete (UHPC) is crucial to ensure bonding strength. Grooving is an effective method to treat the UHPC-NC interface, but the shear properties and failure modes at the interface of the composite remain under-investigated. This study focuses on the bonding performance of different groove designs (width, spacing, and angle) at the UHPC-NC interface, and push-off tests with 15 specimens were carried out to evaluate the strength and stiffness. Further, a finite element model (FEM) was validated with the experimental study to reveal the failure modes and strength-slip curves, and a parametric study on the groove depth was also carried out. Compared with specimens bonded by epoxy resin adhesive, the interface treated by grooves increases 3.32 and 2.48 times in strength and stiffness. The results also show that failing at interface and NC matrix accounted for 80% of failure modes. The shear strength of the UHPC-NC interface increased with the width and decreased with the space between the grooves. It also found certain angles can increase the strength and stiffness by 1.25 and 1.17 times, respectively. When the depth is greater than 25mm, the strength and stiffness will not increase. Grooves with 10mm width, 100mm space, 25mm depth, and right angle were recommended. This paper will lay a foundation for the surface preparation of UHPC strengthening NC bridges.